2011
DOI: 10.1080/00480169.2011.595905
|View full text |Cite
|
Sign up to set email alerts
|

Longevity ofMycobacterium bovisin brushtail possum (Trichosurus vulpecula) carcasses, and contact rates between possums and carcasses

Abstract: Possum carcasses were contacted by free-ranging possums within the period that viable M. bovis were shown to survive in a carcass. The risk of such infection is likely to be most significant in winter or in areas with microhabitats where the survival of M. bovis is high. However, the generally low survival rate of M. bovis in possum carcasses and the low frequency of possum-to-carcass contacts indicate this route of transmission alone could not maintain Tb in a possum population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…the percentage of carcasses consumed) are likely to be overestimates as (1) they do not try to estimate the probability of infection given scavenging (it is assumed to be 1.0), and (2) it is assumed that carcasses are contacted or scavenged within the period that M. bovis bacteria remain viable, as has been found for free-ranging possums encountering dead possums, and for free-ranging possums and ferrets visiting pig remains (Yockney and Nugent 2003 ; Barron et al . 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…the percentage of carcasses consumed) are likely to be overestimates as (1) they do not try to estimate the probability of infection given scavenging (it is assumed to be 1.0), and (2) it is assumed that carcasses are contacted or scavenged within the period that M. bovis bacteria remain viable, as has been found for free-ranging possums encountering dead possums, and for free-ranging possums and ferrets visiting pig remains (Yockney and Nugent 2003 ; Barron et al . 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental studies demonstrate that M. bovis can be isolated >5 months after inoculation when mixed with faeces [176] and after one month in spiked possum carcasses [181]. Viable bacteria were recovered from hay at 7 days after inoculation and could still be isolated from samples of apples, corn and potatoes after 112 days [182].…”
Section: Landscape Climate and Other Environmental Risk Factorsmentioning
confidence: 99%
“…( 2013 ) demonstrated that, for wild possums artificially infected with M. bovis , 61% of the animals had died within 4 months, while Barron et al . ( 2011 ) demonstrated that M. bovis bacilli can remain viable in possum carcasses for only a matter of weeks, even under favourable environmental conditions. A previous study also referred to the survival time of possums following first detection of clinical signs of TB, indicating that this is usually <4 months (Norton et al .…”
Section: Methods For Estimating Possum Populations Following Populatimentioning
confidence: 99%